PERANCANGAN PROSEDUR PEMELIHARAAN AYAM BROILER SESUAI KONSEP 5S UNTUK MENINGKATKAN PRODUKTIVITAS - Indriani, Sri (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2010)
Broiler poultry owned by KUD Sedya Mulya interlaces cooperation with PT. Surya Gemilang Pratama. According to standard given, poultryman is expected to be able to produce broilers and the average of their weight must be 1.85 kilograms for 35 days and also their death rate must be under 5%. According to data records, KUD Sedya Mulya could not complete standard given by its partner. One of way to increase effectiveness and improve productivity is applying a method known by 5S program (Seiri, Seiton, Seiso, Seiketsu, and Shitsuke). This research uses Analytical Hierarchy Process (AHP) method to define the criterias and sub criterias and also prioritise them. The next step is designing some improvement suggestion alternatives according to selected sub criterias based on 5S concept and then choosing the best improvement suggestion alternative and applying it. The last step is comparing productivity of previous raising procedure and productivity of 5S concept applied. According to productivity comparison analysis result, after 5S concept applied, we inform that there is a raising of production by 8.32%, there is a raising of labour productivity by 8.32%, there is a raising of time productivity by 2.19%, there is a raising of food consumed productivity by 16.63%, there is a raising of electricity usage productivity by 15.79%.